Surgical treatment of bronchiectasis: a retrospective observational study of 138 patients - Al-Refaie, Reda E.; Amer, Sameh; El-Shabrawy, Mohamed (Journal of Thoracic Disease, 2013)
Background: We analyzed cases of bronchiectasis; its presentation, etiology, diagnosis, indications for surgery, surgical approach, and the outcome. Methods: A retrospective analysis of 138 patients who underwent surgery for bronchiectasis. Results: The mean age was 30.2±15.7 years. 55.8% patients were males. Symptoms were recurrent infection with cough in all patients, fetid sputum (79.7%), and hemoptysis (22.5%). The etiology was recurrent childhood infection (38.4%), pneumonia (29%), TB (9.4%), sequestration (4.3%), foreign body obstruction (4.3%), and unknown etiology (14.5%). CXR, CT scan, and bronchoscope were done for all patients. Bronchiectasis was left-sided in (55.1%) of patients. It was mainly confined to the lower lobes either alone (50.7%) or in conjunction with middle lobe or lingual (7.2%). Indications for resection were failure of conservative therapy (71.7%), hemoptysis (15.9%), destroyed lung (8%), and sequestration (4.3%). Surgery was lobectomy (81.2%), bilobectomy (8.7%), and pneumonectomy (8%). Complications occurred in 13% with no operative mortality. 84% of patients had relief of their preoperative symptoms. Conclusions: Surgery for bronchiectasis can be performed with acceptable morbidity and mortality at any age for localized disease. Proper selection and preparation of the patients and complete resection of the involved sites are required for the optimum control of symptoms and better outcomes.